Karakterisasi, Kesesuaian Lahan dan Teknologi Kelapa Sawit Rakyat di Rawa Pasang Surut Kalimantan Tengah - M. Anang Firmansyah (Politeknik Negeri Lampung., 2014)
Oil palm extensification in tide land. It’s a marginal land which sensitive to degradation. Otherwise, peat is low bearing capacity, subsidence, drying irreversible and close fire and then emission of green house gas. So other soil in the tide land is acid sulfate soils have a pyrite, while be can oxidation can produce of increased soil acidity and ferro and aluminum. Location of research include ine Ex Rice Mega Project ie. Kapuas Regency and Pulang Pisau Regency, and other is East Kotawaringin Regency. Limiting factor in soil mineral are effective dept of soil and drainage class (S3-d2.s2 dan s2-d2); and then in peatland are soil dept, decomposition factor and drainage class (S3-t2.d2, S3-s2d2 dan S3-d2). Agronomic action used farmer and plantation industry very variance, so characteristic and climate quality, land, agronomic, post harvest wil can level of agronomic compound of oil palm in tide land wich better for produce, efficiency, and green environment. Keywords: Oil palm, tidal swamp, Central Kalimantan